Pelatihan Budidaya Lebah Apis cerana pada Kelompok Tani Mekar di Desa Timpuseng Kabupaten Maros - Nuraeni, Sitti; Supratman, Supratman; Mujetahid, Andi; Rijal, Syamsu; Rifky Makkasau, Ahmad; Prastiyo, Andi; S, Harlina (Lembaga Dongan Dosen, 2024)
Management of honey bees, especially Apis cerana bees, is widely cultivated by farmers in Sulawesi. Lack of cultivation knowledge and management causes productivity to decrease. A. cerana bee cultivation training at the Mekar Farmers Group in Timpuseng Village, Maros Regency, aims to increase farmers' knowledge and skills in bee colony management, honey harvesting techniques and processing of bee products. This training method includes socialization, presentation of material, discussion and evaluation. Based on data, the majority of farmers (70%) harvest honey by pressing it, while 50% of farmers increase their colonies by dividing existing colonies, and the other 50% hunt in the forest. However, only 30% of farmers were able to differentiate between bee products such as honey, beeswax and bee bread, indicating the need for additional education. This training uses a practical approach to support environmentally friendly colony management and diversification of bee products as added economic value. Evaluation results show that this training contributes significantly to improving farmers' technical skills, encouraging the adoption of sustainable methods, and supporting the preservation of local ecosystems. The training participation rate reached 70%, indicating the high interest of farmers in developing bee cultivation. This training provides a strong foundation for the development of independent and sustainable bee-based businesses.